Introduction To The Types of Pollutants Included In Greenhouse Gases In The Context of Understanding And Addressing Climate Change In Penang, Malaysia - Nurato Nurato; I G Ayu Arwati; Muhammad Fitri (International Journal Of Community Service, 2025)
Climate change is a global challenge that requires a thorough understanding of greenhouse gas (GHG) pollutants. Gases such as carbon dioxide (CO₂), methane (CH₄), and nitrous oxide (N₂O) trap heat in the atmosphere, causing global warming with serious consequences such as extreme weather events and ecosystem disruption. The main sources of emissions come from the energy, industrial, agricultural, and land-use change sectors. This paper emphasizes that identifying the types of GHG pollutants and their characteristics is crucial for developing targeted mitigation strategies. These efforts, which include a transition to renewable energy, increased energy efficiency, and strong policy implementation, are expected to significantly reduce global emissions, stabilize the climate, and control the rate of warming.